2019
DOI: 10.1098/rsob.190141
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel regulatory pathway for PPARα by RNA-seq characterization of the endothelial cell lipid peroxidative injury transcriptome

Abstract: Endothelial dysfunction caused by endothelial cell injuries is the initiating factor for atherosclerosis (AS), and lipid peroxidative injury is one of a dominant factor for AS pathogenesis. Using RNA-seq, we compared changes in transcriptome expression before and after endothelial cell injury, and found 311 differentially expressed genes (DEGs), of which 258 genes were upregulated and 53 genes were downregulated. The protein–protein interactions (PPIs) between the genes were analysed using the STRING database,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Clinical experiments have found significantly reduced levels of plasma interleukin-6 (IL-6), interferon- α (IFN- α ), and C-reactive protein (CRP) after taking the PPAR α agonist (fibrate) in patients with coronary heart disease confirmed by angiography [ 14 ]. Our previous research confirmed that PPAR α promotes the repair of endothelial cell injury by upregulating CCL2 expression in human umbilical vein endothelial cells [ 15 ]. Some research reported that Tongxinluo protects diabetic hearts against ischemia/reperfusion injury by activating Angptl4-mediated restoration of endothelial barrier integrity via the PPAR α pathway [ 16 ].…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Clinical experiments have found significantly reduced levels of plasma interleukin-6 (IL-6), interferon- α (IFN- α ), and C-reactive protein (CRP) after taking the PPAR α agonist (fibrate) in patients with coronary heart disease confirmed by angiography [ 14 ]. Our previous research confirmed that PPAR α promotes the repair of endothelial cell injury by upregulating CCL2 expression in human umbilical vein endothelial cells [ 15 ]. Some research reported that Tongxinluo protects diabetic hearts against ischemia/reperfusion injury by activating Angptl4-mediated restoration of endothelial barrier integrity via the PPAR α pathway [ 16 ].…”
Section: Introductionsupporting
confidence: 62%
“…Some research reported that PPAR γ protects against vascular aging [ 27 ], but there were few studies on the correlation between PPAR α and aging. Our previous RNA sequence research found that PPAR α was involved in the regulation of damaged vascular endothelial cell repair [ 15 ]. The causes of endothelial cell aging mainly include cell replication aging and stress-induced cell premature senility.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lipid peroxidation mediated by endogenous factors, such as NADPH oxidases, reactive oxygen species, lipoxygenases and xanthine oxidase, and exogenous reagents, such as cigarette smoking, UV‐light, and air pollution, results in more oxidized lipids (e.g., oxidized LDL) to produce pro‐inflammatory effects on endothelium and macrophages 59 . PPARα overexpression accelerates endothelial repair after lipid peroxidative‐induced injury in a C─C motif chemokine ligand 2‐dependent mechanism 60 …”
Section: The Role Of Pparα In Endothelial Function and Vascular Diseasesmentioning
confidence: 99%
“…59 PPARα overexpression accelerates endothelial repair after lipid peroxidative-induced injury in a C─C motif chemokine ligand 2-dependent mechanism. 60 Insulin resistance is an important risk factor of endothelial activation, which is defined as a lack of sensitivity or responsiveness to insulin-mediated actions such as glucose disposal and vascular tone regulation. 61 Insulin resistance is a prominent element of obesity and type 2 diabetes, where both are associated with endothelial dysfunction.…”
Section: Pparα Is a Therapeutic Target To Inhibit Endothelial Inflamm...mentioning
confidence: 99%
“…A transcriptome is all the transcripts produced in cells under specific physiological conditions and reveals the molecular mechanism of specific biological processes (Dou et al, 2019). High-throughput mRNA sequencing (RNA-Seq), an ultrahigh-throughput sequencing technology for transcriptomic analysis, has been widely used to reveal the gene expression changes of non-model organisms that lack reference genome information (Grabherr et al, 2011).…”
Section: Introductionmentioning
confidence: 99%